2017
DOI: 10.1016/j.foodchem.2017.03.048
|View full text |Cite
|
Sign up to set email alerts
|

The influence of pre-fermentative maceration and ageing factors on ester profile and marker determination of Pedro Ximenez sparkling wines

Abstract: The influence of pre-fermentative maceration and ageing factors on the ester profiles of Pedro Ximenez sparkling wines was evaluated. The pre-fermentative maceration consisted of the skin-maceration of musts at 10°C for 6h. The sparkling wines were produced following the Champenoise method. Samples were monitored at 3, 6 and 9months of ageing on lees. Sparkling wines with pre-fermentative maceration displayed higher contents of ethyl esters of branched acids and cinnamates. Meanwhile, those without maceration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 35 publications
4
15
1
1
Order By: Relevance
“…In the flor yeast, a significant decrease in the amount of most acetate esters was observed during the second fermentation, except for methyl acetate, whose concentration increased, and isobutyl acetate that was not identified. The concentration of the rest of acetate esters remained without significant differences during this study; except hexyl acetate that decreased as in the studies carried out by other authors [53].…”
Section: Acetate Esterssupporting
confidence: 75%
“…In the flor yeast, a significant decrease in the amount of most acetate esters was observed during the second fermentation, except for methyl acetate, whose concentration increased, and isobutyl acetate that was not identified. The concentration of the rest of acetate esters remained without significant differences during this study; except hexyl acetate that decreased as in the studies carried out by other authors [53].…”
Section: Acetate Esterssupporting
confidence: 75%
“…The highest concentration of total phenolic compounds in the CB+SY-R sparkling wine can be justified by the pre-fermentative maceration occurred. In a study with Spanish sparkling wines with Pedro Ximenez variety, Ruiz-Moreno et al [23] also observed higher concentration of total polyphenols in the sparkling wine whose must has been pre-fermentative macerated. In the same way, the absorption at 420 nm (yellow) was higher for the CB+SY-R sparkling wine.…”
Section: Classical Enological Parameters and Antioxidant Activitymentioning
confidence: 93%
“…Nonetheless, an ample range of carbohydrates with different monosaccharide content and configuration of glycosidic linkages could exhibit potential prebiotic effect. Novel prebiotic compounds could derive from natural and renewable resources or synthesized enzymatically [259]. Dietary fibers and their hydrolysis products are becoming an emerging source of new ingredients with potential prebiotic activity.…”
Section: Development Of Synbioticsmentioning
confidence: 99%